(3i)-(6i)=0

Simple and best practice solution for (3i)-(6i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3i)-(6i)=0 equation:


Simplifying
(3i) + -1(6i) = 0

Remove parenthesis around (6i)
(3i) + -1 * 6i = 0

Multiply -1 * 6
(3i) + -6i = 0

Combine like terms: (3i) + -6i = -3i
-3i = 0

Solving
-3i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Divide each side by '-3'.
i = 0

Simplifying
i = 0

See similar equations:

| 7=8y-17 | | 3(b+3)=42 | | (x^2)-x+400=0 | | 2(a-3)=40 | | 0.34=lnx | | 6x-1=125 | | 2+x+3x=34 | | y=x(x-2y)+2y(x+2y) | | -4x^2+11x-6=o | | (x^2)-x+20=0 | | 16q-18=qr+t | | 5x+6-x=-30 | | 0.5x+7=-9 | | G-24=14 | | x^3-12x^2+230.4=0 | | 25+4y=25+16 | | 5x-3(x-3)=4+5x-8 | | 0.5x+6=17 | | -4(6x-7)=-24x-28 | | -12x-65=-7x | | 5-(2x+2)=-(-3x+5)-x | | 3(-2x+5)=9 | | 1x+.5y=6 | | 21=7y+7+(y+3) | | 7(-6x+1)=-329 | | X-2(x+3)=-2(x+1)-4 | | 2x+1+3x=30 | | x=a(a-b)+b(a+b) | | x=-3+13 | | 2x-3+19=17 | | 5x=63.25 | | [2x+3]=-5 |

Equations solver categories